PENGARUH ENVIRONMENTAL CONSCIOUSNESS, ECO-LABEL, ATTITUDE, GREEN ADVERTISING, PRICE TERHADAP BUYING DECISION OF GREEN PRODUCTS (STUDI PADA KONSUMEN GENERASI Z THE BODY SHOP DI KOTA BANDUNG) - Aprilia Diahayu Ningtias; Citra Dewi (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. The increasing number of beauty products being sold and used is creating a higher amount of plastic waste. Plastic waste from skincare or cosmetic packaging if not managed and recycled properly, plastic waste will accumulate and become an environmental problem. The Body Shop since the beginning introduced its products as green products, offering products with natural ingredients, environmentally friendly and not testing on animals. The purpose of this study was to determine how the influence of Environmental Consciousness, Eco-Label, Attitude, Green Advertising, Price on Buying Decision of Green Products on generation Z consumers of The Body Shop in Bandung City both partially and simultaneously. This research data collection through distributing questionnaires and using quantitative data analysis. Sampling was carried out using nonprobability sampling method using purposive sampling technique. The sample used in this study was 100 respondents and analyzed by multiple linear regression analysis with the help of SPSS software version 25.Based on the results of data processing, it is concluded that partially Environmental Consciousness and Price have a positive and significant effect on Buying Decision of Green Products. Eco-Label has no significant effect on Buying Decision of Green Products. Attitude and Green Advertising partially have a positive effect and there is no significant effect on Buying Decision of Green Products. Environmental Consciousness, Eco-Label, Attitude, Green Advertising, and Price simultaneously have a significant positive effect on Buying Decision of Green Products.. Abstrak. Semakin meningkatnya jumlah produk kecantikan yang dijual dan dipakai turut menciptakan jumlah sampah plastik yang lebih tinggi. Sampah plastik dari kemasan skincare atau kosmetik jika tidak dikelola dan didaur ulang dengan baik, sampah plastik akan menumpuk dan menjadi masalah lingkungan. The Body Shop sejak awal memperkenalkan produknya sebagai green product, menawarkan produk dengan bahan-bahan alami, ramah lingkungan dan tidak melakukan uji coba kepada hewan. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengaruh dari Environmental Consciousness, Eco-Label, Attitude, Green Advertising, Price terhadap Buying Decision of Green Products pada konsumen generasi Z The Body Shop di Kota Bandung baik secara parsial maupun secara simultan. Pengumpulan data penelitian ini melalui penyebaran kuesioner dan menggunakan analisis data kuantitatif. Pengambilan sampel dilakukan dengan menggunakan metode nonprobability sampling dengan teknik purposive sampling. Sampel yang digunakan dalam penelitian ini sebanyak 100 responden dan dianalisis dengan analisis regresi linier berganda dengan bantuan software SPSS versi 25. Berdasarkan hasil pengolahan data didapatkan kesimpulan bahwa secara parsial Environmental Consciousness dan Price berpengaruh positif dan signifikan terhadap Buying Decision of Green Products. Eco-Label tidak terdapat pengaruh signifikan terhadap Buying Decision of Green Products. Attitude dan Green Advertising secara parsial berpengaruh positif dan tidak terdapat pengaruh signifikan terhadap Buying Decision of Green Products. Environmental Consciousness, Eco-Label, Attitude, Green Advertising, dan Price berpengaruh signifikan positif secara simultan terhadap Buying Decision of Green Product.